Correlation of tilt of the anterior pelvic plane angle with anatomical pelvic tilt and morphological configuration of the acetabulum in patients with developmental dysplasia of the hip: a cross-sectional study - Norio Imai; Hayato Suzuki; Asami Nozaki; Yuki Hirano; Naoto Endo (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background It was previously reported that pelvises with developmental dysplasia of the hip are tilted anteriorly, which increases bony coverage of the femoral head. This study aimed to investigate the correlation between anatomical parameters of the pelvis such as pelvic incidence and anatomical pelvic tilt and functional parameters of the spine and pelvis such as tilt of the anterior pelvic plane. Methods We examined 84 female patients with bilateral developmental dysplasia of the hip who had undergone curved periacetabular osteotomy at author’s institution. Radiographs of the thoracic to lumbar spines and the pelvis were obtained in the standing position to measure spino-pelvic parameters before surgery. Morphological parameters of the acetabulum such as the anterior center-edge (CE) angle, posterior CE angle, lateral CE angle, and acetabular anteversion were measured using a preoperative three-dimensional pelvic model reconstructed from computed tomography images. Pearson’s correlation analysis was conducted to evaluate the relationship of these parameters. Results With regard to correlations between pelvic incidence (PI) and other parameters, the sacral slope (SS) value (r = 0.666) was the highest among functional parameters and the anatomical-SS value (r = 0.789) was the highest among morphological parameters. There were moderate correlations of the anterior pelvic plane angle (APPA) with pelvic tilt (PT) (r = − 0.594) and anatomical-PT (r = 0.646). With regard to correlations between spino-pelvic parameters and bony morphological parameters of the acetabulum, there was a moderate correlation between anatomical-PT and acetabular anteversion (AA) (r = 0.424). There were moderate correlations of APPA with the anterior CE angle (r = − 0.478), posterior CE angle (r = 0.432), and AA (r = 0.565). APPA had a stronger correlation with anatomical-PT (r = 0.646) than with AA. Conclusions The tilt of the pelvis may be more dependent on anatomical-PT, a morphological parameter of the pelvis, than the lateral CE angle, anterior CE angle, posterior CE angle, and acetabular anteversion on bony coverage of the acetabulum. This study is the first to investigate the correlation between functional parameters of the pelvis and spine and morphological parameters of the pelvis and acetabulum besides PI.